The effect of banning affirmative action on human capital accumulation prior to college entry - Kate L. Antonovics; Benjamin Backes (IZA Journal of Labor Economics, 2014)
This paper examines how banning affirmative action in university admissions affects both overall academic achievement and the racial gap in academic achievement prior to college entry. Focusing on college-bound high school students, we use a difference-in-difference methodology to analyze the impact of the end of race-based affirmative action at the University of California in 1998 on both the overall level of SAT scores and high school GPA, and the racial gap in SAT scores and high school GPA. We find little evidence of either a decline in academic achievement or a widening of the racial gap in academic achievement after the ban.
Keywords: I21; I24; 330; Education; Inequality; Education policy; Affirmative action